THE TRAINING KNOWELDGE NEEDS FOR BARLEY GROWERS TO MANAGE THEIR CROP AT AL-SHIHIMIYA TOWNSHIP – ALSWIRA TOWN –WASIT GOVERNORATE - Hassuny, A. R. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research aimed to determine the level of training knowledge needed for barley growers to manage their crop at Al-shihimiya Township –Alswira Town -Wasit Governorate.The training knowledge needed aimed to cover all crop management axes which included land preparation, date of seeding fertilizer and pesticides application, irrigation and harvest, to recognize the most important problems faced by barley growers during growing period. To archive that goal a randomized sample was taken 5% from the growers’ population 2126 (i.e. the sample size was 106 growers). The statistical analysis covered 100 growers and data collected through questionnaires sheet .This sheet included two parts: 1st one aimed to test the training knowledge needed for barley growers to manage their crop at the field through 47 paragraphs distributed to 6 axises which included land preparation ,date of seeding fertilizer and pesticides application ,irrigation and harvest. The 2nd part included 12 suggested problems facing barley growers during crop management. Results indicated that 51% of the questioned growers had high training qualifications and this represent 117.49 grade on the scale of 0-141 for training knowledge needed .The most problems facing the growers is the delay in receiving their money dues with an important grade of 3. The 2nd faced problem growers faced was the import of barley crop by the government which had 1.89 grades. Therefore, it can be con concluded that Ministry of Agriculture (MOA) have to activate the role of agriculture extension through their personals available at the ministry directorates and extension centers through training programs and extension activities related mainly to strategic crop in general and barley crop in particular and encourage growers to join such this activities .Furthermore, MOA should provide agricultural chemicals and agricultural equipments as a part of the subsidizing program Iraqi government have and help farmers to collect their grains and make sure to pay for it at the right time from the MAO and the Ministry of Trade (MOT) due to the dependence of those growers on this income for their life support